(untitled) (Práxis Educativa, 2024)
Youth and Adult Education (known by the acronym EJA, in Portuguese) is not always understood and developed adequately. It is often taken as a compensatory measure when, in fact, it is a social right. This article aims to investigate the contributions of the development of the Freirean dialogicity, through an extracurricular course, in the initial education of Mathematics teachers to work at EJA. The course was developed at the Instituto Federal Fluminense (IFF), Campos Centro campus, with nine Mathematics pre-service teaching undergraduate students who were part of the 2020 CAPES Pedagogical Residency Program. The development and implementation of the course were based on the Progressive Liberating pedagogical concept, founded by Paulo Freire. The methodology used was applied, qualitative and exploratory. In view of the analysis of the results, it was possible to consider that the course promoted several contributions to the participants’ initial education and that there is the possibility of the training sparking new dialogues in other contexts. Keywords: Youth and Adult Education. Mathematics teaching. Dialogicity.